ANALISIS PENGARUH CAR, FDR, NPF, BOPO TERHADAP PROFITABILITAS BANK SYARIAH (ROA) (Students' Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Operation Efficiency (ROA) for the Return On Asset (ROA) as a proxy of profitability Islamic Bank in Indonesia during the 2011-2014 period. This study uses 4 samples Islamic Bank - Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank Mega Syariah and BNI Syariah. Data analysis technique used in this study is multiple regression. These results indicate that CAR has a significant negative influence and affect the ROA. FDR and NPF has a negative and significant impact on ROA. Meanwhile, the variable ROA has a positive and significant effect on ROA. Predictive ability of the four variables on ROA of 34,4%, while the rest influenced by other factors outside the research model. Research is expected to be a guideline for the management of Bank Islam in managing their companies.Keywords: Profitability, CAR, FDR, NPF, BOPO, ROA